Handbook of sustainable development - Neumayer, Eric 1970-; Atkinson, Giles 1969-; Dietz, Simon (Edward Elgar, 2007)
This timely and important Handbook takes stock of progress made in our understanding of what sustainable development actually is and how it can be achieved. Twenty years on from the publication of the seminal Brundtland Report, it has become clear that formidable challenges confront policy makers who have publicly stated their commitment to the goal of sustainable development. The Handbook of Sustainable Development seeks to provide an account of the considerable progress made in fleshing out these issues
Includes bibliographical references and index
Keywords: Nachhaltigkeit; Umweltökonomie; Sustainable development; Aufsatzsammlung